A Meaningful Life amidst a Pluralism of Cultures and Values : John Lachs's Stoic Pragmatism as a Philosophical and Cultural Project - Skowroński, Krzysztof Piotr, (Value Inquiry Book Series ;, 2023)
There is a growing concern about living a meaningful life among those living in different contexts of cultural diversity, be it the American melting pot, the union of European nations, the multiculturally globalized, the multiformity of tribalism of various stripes, and the fashionable cyber bubbles of opinion and commentary that drive the outlooks of millions of uninformed consumers. This book argues for a wisdom that incorporates a reference for both knowledge and self-knowledge, as well as life experience and cultural traditions that have stood the test of time, all contributing to a framework in which we can navigate our lives.